1996
DOI: 10.1597/1545-1569_1996_033_0067_nsfonm_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Stimuli for Obtaining Nasalance Measures from Young Children

Abstract: The use of novel stimuli for obtaining nasalance measures in young children was the focus of this study. The subjects were 20 children without a history of communication disorders and 20 children at risk for velopharyngeal insufficiency (VPI). Each subject recited three passages; the standard Zoo Passage, and two novel stimuli that were named the Turtle Passage and the Mouse Passage. Like the Zoo Passage, the Turtle Passage contained no normally nasal consonants. The Mouse Passage was about 11% nasal consonant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 12 publications
1
18
0
8
Order By: Relevance
“…The Turtle Passage contains 29 syllables and has been shown to be comparable to the longer Zoo Passage with respect to nasalance scores obtained (Watterson et al, 1996). Like the Zoo Passage, the Turtle Passage contains no nasal consonants.…”
Section: Stimulimentioning
confidence: 80%
“…The Turtle Passage contains 29 syllables and has been shown to be comparable to the longer Zoo Passage with respect to nasalance scores obtained (Watterson et al, 1996). Like the Zoo Passage, the Turtle Passage contains no nasal consonants.…”
Section: Stimulimentioning
confidence: 80%
“…Studien haben gezeigt, dass die Nasalanz durch die phonetische Zusammensetzung des Sprachstimulus [5,23], wie an dem vorliegenden Untersuchungsgut gezeigt werden konnte, die Muttersprache [1,11,15], regionale Dialekte [11,17], das Geschlecht [4,11,17], das Alter [9,11] und die Rasse [13] beeinflusst wird. Demgegenüber fanden aber Van Doorn u. Purcell [20] sowie Litzaw u. Dalston [12] keine Geschlechts-und Altersabhängigkeiten.…”
Section: Diskussionunclassified
“…Watterson et al [23] fanden für einen Text ohne Nasallaute (Zoopassage) bei amerikanischen Kindern eine mittlere Nasalanz von 15,4%. Für die spanische Sprache wurde ein Mittelwert der Nasalanz von 36% für einen gemischten Text angegeben [1].…”
Section: Introductionunclassified
“…However, as Kent (1996) also points out, multiple variables, including articulation, fluency, and phonology of the speakers, can affect listeners' perceptual judgment, compromising the validity of the perceptual evaluation. Fletcher et al (1989) and Watterson et al (1996) also noted that the phonetic context of the speech sample influenced the perceptual judgment of hypernasality. Furthermore, early research (e.g., Bradford et al, 1964) showed that the reliability of perceptual judgments might be problematic even for ''experienced'' judges of hypernasality.…”
mentioning
confidence: 99%